Peran Edukasi Etika Digital Dalam Mengurangi Risiko Serangan Keamanan Informasi - Alfina Elsa Putri; Nazori Suhandi (CV. SINAR HOWUHOWU, 2026)
Digital ethics education is becoming increasingly important with the increasing threat of cybercrime and the need to protect personal data in the digital age. This study aims to analyze the role of digital ethics education and digital literacy in reducing the risk of security attacks. Using a literature review method, the study gathered information from journals, books, and reports related to digital ethics, data security, and user behavior. The results show that digital ethics education, which includes an understanding of the safe, legal, and responsible use of technology, can increase public awareness of cyber threats and strengthen their ability to maintain data integrity and privacy. The use of information technology in the educational process has also proven effective in encouraging ethical digital behavior, reducing the opportunity for attacks such as phishing, social engineering, and data misuse. Therefore, digital ethics education plays a crucial role in shaping a society that is intelligent, critical, and safe in its digital activities, thereby significantly reducing the risk of information security incidents.